ANALYZING ENGLISH TEACHERS’ INSTRUCTION AND MEDIA INVOLVEMENT OF BLENDED LANGUAGE LEARNING IN HIGHER EDUCATION - Purnawati, Purnawati; Forsia, Lastry; Shopia, Khilda (Universitas Muhammadiyah Metro, 2023)
Previous researchers have widely investigated the analysis of teachers’ instruction as a micro-learning. These researches need to be continued by analyzing other teaching aspects such as the involvement of learning media and blended learning model. Therefore, this study aims to analyze the teachers’ instruction in Higher Education by using learning media in the context of the blended learning model. By employing a qualitative descriptive analysis approach, this research examined five samples of blended classes’ instruction, including two online synchronous learning, one offline synchronous learning, and two online asynchronous learning. These samples are observed, transcribed, and analyzed to highlight the specific instruction in the classes.Meanwhile, the employment of learning media was gathered using an interview with the teachers. The result of data analysis found that various teachers’ instruction can be implemented in synchronous and asynchronous classes of blended learning context to support students centered learning. Meanwhile, slide shows, Zoom, G-meet, and LMS are the media often used. Moreover, blended learning can support student-centered learning as well as offline learning. This finding contributes to the student-centered approach implementation, which aligns with the 21st-century learning model.